A non-ideal portal frame energy harvester controlled using a pendulum - Iliuk, I.; Balthazar, José Manoel [UNESP]; Tusset, A. M.; Piqueira, J. R C; Rodrigues de Pontes, B. [UNESP]; Felix, J. L P; Bueno, Á [UNESP] (Springer Nature, 2013)
A model of energy harvester based on a simple portal frame structure is presented. The system is considered to be non-ideal system (NIS) due to interaction with the energy source, a DC motor with limited power supply and the system structure. The nonlinearities present in the piezoelectric material are considered in the piezoelectric coupling mathematical model. The system is a bi-stable Duffing oscillator presenting a chaotic behavior. Analyzing the average power variation, and bifurcation diagrams, the value of the control variable that optimizes power or average value that stabilizes the chaotic system in the periodic orbit is determined. The control sensitivity is determined to parametric errors in the damping and stiffness parameters of the portal frame. The proposed passive control technique uses a simple pendulum to tuned to the vibration of the structure to improve the energy harvesting. The results show that with the implementation of the control strategy it is possible to eliminate the need for active or semi active control, usually more complex. The control also provides a way to regulate the energy captured to a desired operating frequency. © 2013 EDP Sciences and Springer.